IMPACT OF READING AND WRITING ON SCHOOL COEXISTENCE: AN APPROACH TO THE IMMINENT REALITY OF EDUCATIONAL INSTITUTIONS IN THE COLOMBIAN CONTEXT - José Jamir collazos Lozada; Adriana Milena Noreña Salazar (LÍNEA IMAGINARIA, 2025)
Education today is facing countless changes and transformations that occur in everyday life; it is worth mentioning the era we live in today with the inclusion of technology in the educational system; assuming that artificial intelligence has taken over multiple processes that arise from the pedagogical fact; considering that from this perspective it is necessary to rethink the following general objective: to reflect on the impact of reading and writing on school coexistence as an approach to the imminent reality of educational institutions in the Colombian context. The methodology used is framed in a documentary analysis, which leads to a systematic review of bibliography which brings as a product a scientific essay that becomes a significant contribution for teachers to have at hand a set of theoretical elements that converge in actions and pedagogical activities that go in function of correcting countless elements that alter the peaceful coexistence that from the reading and writing lead to establish an approach on the imminent reality of educational institutions.